PENGEMBANGAN BAHAN AJAR E-BOOK BERBANTUAN 3D PAGEFLIP PROFESIONAL PADA PEMBELAJARAN MENULIS TEKS EKSPLANASI - Hayati, Nur (Mutiara Guru: Jurnal Model Pembelajaran, 2022)
purpose of writing this article is to (1) describe the meaning of teaching materials (2) describe the professional 3D phageflip e-book application (3) describe the discussion of research results using the learning device development model, namely the ADDIE model which includes five things, namely: Analysis, design , development, implementation, and evaluation. This research uses a descriptive descriptive method that does not require statistics. This method is carried out by collecting library data and then studying it. E-Module Development Digital teaching materials using e-book teaching materials assisted by 3D Pageflip Professional in Indonesian subjects were developed through research and development (R&D) research. The process of developing e-book teaching materials is assisted by 3D Pageflip Professional. carried out through several stages before producing learning media that is good and suitable for use in the learning process to achieve the minimum completeness criteria (KKM). Teaching materials using e-books assisted by 3D Pageflip Professional are new innovations to facilitate the learning process and receive positive responses from students because they simplify the learning process. This shows that learning using 3D Pageflip Professional assisted teaching materials can be a solution in the learning process.